Retrospective study on the pathological changes and bacterial isolations in small ruminants diagnosed with pneumonia - Zakaria, Muhamad Alif (2018)
The cause and type of pneumonia in small ruminant have not been reported in Malaysia. Hence, it is imperative to investigate the incidence and type of pneumonia commonly observed in small ruminants. This investigation was carried out on 94 pneumonic cases involving 299 small ruminant carcasses presented for necropsy at the Department of Veterinary Pathology & Microbiology, Universiti Putra Malaysia, during a 10-year period between 2008 and 2017. The gross and histopathology lesions and the associated bacterial isolations were obtained from the records. The specific type of pneumonia was diagnosed by histopathological examination of selected lungs tissues, using standard techniques. The results of the bacterial isolates (n=134) revealed Escherichia coli (29.1%), Pasteurella spp. (17.1%), Klebsiellapneumoniae (15.6%), Staphylococcus aureus (6.7%) and Mannheimia spp. (5.9%) as common isolates. The gross lesions of pneumonic lungs included congestion, consolidation and exudation. Three types of pneumonia were identified based on the histopatholological examinations, which were suppurative bronchopneumonia 71 (75.53%), fibrinous bronchopneumonia 7 (7.45%), interstitial pneumonia 3 (3.19%) and others 13 (13.93%).